Command Filter-Based Finite-Time Adaptive Fuzzy Control for Uncertain Nonlinear Systems With Prescribed Performance - Sun, Wei; Wu, Yu-Qiang; Sun, Zong-Yao (IEEE transactions on fuzzy systems, 2020)
This article reports our study on the issue of finite-time adaptive fuzzy tracking control for a class of uncertain nonlinear systems with the prescribed performance. A novel finite-time prescribed performance control approach, in which fuzzy systems are employed to approximate completely unknown nonlinear functions, is proposed by incorporating the technique of prescribed performance control with the method of command filtered design. Based on the finite-time stability theory, all the signals of the closed-loop system can be bounded and the output tracking error can converge to a prescribed small region within a finite-time by the proposed scheme; meanwhile, the problem of complexity explosion can be avoided. The effectiveness of the presented method is verified by two examples.